1990
DOI: 10.1126/science.2148832
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Neurotoxins by Mononuclear Phagocytes Infected with HIV-1

Abstract: Mononuclear phagocytes (microglia, macrophages, and macrophage-like giant cells) are the principal cellular targets for human immunodeficiency virus-1 (HIV-1) in the central nervous system (CNS). Since HIV-1 does not directly infect neurons, the causes for CNS dysfunction in acquired immunodeficiency syndrome (AIDS) remain uncertain. HIV-1-infected human monocytoid cells, but not infected human lymphoid cells, released toxic agents that destroy chick and rat neurons in culture. These neurotoxins were small, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
317
0
4

Year Published

1991
1991
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 604 publications
(333 citation statements)
references
References 44 publications
12
317
0
4
Order By: Relevance
“…[1][2][3]7,15 This leads to toxin production by these monocytic cells, which seems essential for a pronounced neurodegenerative effect. 7,11,[16][17][18] Indeed, we and others have observed earlier that gp120 neurotoxicity was virtually absent if microglia were either removed from mixed cerebrocortical cultures or inactivated. 10,11,18,19 This finding strongly suggested a critical role for microglial HIV-1 coreceptors in the generation of neurotoxicity.…”
mentioning
confidence: 73%
“…[1][2][3]7,15 This leads to toxin production by these monocytic cells, which seems essential for a pronounced neurodegenerative effect. 7,11,[16][17][18] Indeed, we and others have observed earlier that gp120 neurotoxicity was virtually absent if microglia were either removed from mixed cerebrocortical cultures or inactivated. 10,11,18,19 This finding strongly suggested a critical role for microglial HIV-1 coreceptors in the generation of neurotoxicity.…”
mentioning
confidence: 73%
“…Manifestations of ADC are progressive cognitive, motor, and behavioral dysfunctions that have been linked to the persistence of HIV-1 infections in the CNS and are mainly found in CD4-positive (CD4+) microglial cells and circulating macrophages (Budka, 1991;Fauci, 1988;Jordan et al, 1991;Ketzler et al, 1990;Liu et al, 1990;Maddon et al, 1986;McArthur, 1987;Merrill and Chen, 1991;Price et al, 1988). However, in the absence of CD4 molecules on the cell membrane of the majority of brain cells and in the light of the paucity of direct evidence for HIV infection of neurons and glial cells it has been suggested that the HIV-associated degenerative neurological abnormalities are the result of indirect mechanisms mediated by soluble factors of viral or cellular origin (Brenneman et a/., 1988;Dreyer et al, 1990;Giulian et al, 1990;Kaiser et al, 1990;Pulliam et al, 1991;Wahl et al, 1991 ). These factors could be cytotoxic to Subpopulations of brain cells or interfere with neuronal and glial cell functions leading to neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, ciertos estados patológicos, entre ellos la infección por el VIH-1, generan una producción no regulada de estos factores, lo que produce alteraciones en el desarrollo neurológico. En este mismo sentido, varias investigaciones recientes señalan que mediadores solubles producidos por monocitos/ macrófagos de pacientes infectados con el VIH-1, alteran el crecimiento y la supervivencia de las neuronas y de las células gliales inmaduras en cultivo (44)(45)(46). Se han documentado niveles alterados de IL-1, IL-6, TNF-a y MCP-1 en el líquido cefalorraquídeo (LCR) de pacientes con sida, tanto adultos como pediátricos (47)(48)(49).…”
Section: Mediadores Inmunológicos Y Proteínas Virales Solubles Actorunclassified